An update on regional analgesia for rib fractures. Issue 5 (October 2018) - Thiruvenkatarajan, Venkatesan; Cruz Eng, Hillen; Adhikary, Sanjib Das
Abstract : Purpose of review: To provide an update on new strategies for pain management after rib fractures utilizing regional analgesia. Recent findings: Pain management for patients with rib fractures can be very challenging. Traditionally, intravenous patient-controlled analgesia (IVPCA) with opioids, epidural, and paravertebral blocks have been used. These techniques, however, may be contraindicated or have limited application in certain patient populations. Recently, ultrasound-guided myofascial plane blocks such as the erector spinae plane (ESP) block and the serratus anterior plane (SAP) block have emerged as alternatives; providing excellent analgesia with minimal side effects. These blocks have the flexibility to be employed in a wide variety of circumstances where epidural and paravertebral approaches may not be feasible such as in anticoagulated patients and in patients with vertebral fractures where positioning options are limited. Myofascial blocks are less invasive and allow for broader and earlier application (e.g. in the emergency department). Further research on myofascial plane blocks is a priority. Summary: Until recently, epidural, paravertebral, and intercostal blocks have been advocated as primary management techniques for pain associated with rib fractures. Newer myofascial plane blocks may play a key role in the future as part of alternative pain management strategies.